TRANSFORMASI KEPEMIMPINAN PENDIDIKAN ISLAM: TANTANGAN DAN PELUANG DI ERA DIGITAL - Ilham Yahya Romandoni; Sulistyorini; Nur Efendi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
The digital era has brought significant changes in various aspects of life, including in the field of education. The leadership of Islamic education is no exception, which faces challenges as well as opportunities in carrying out its role in the midst of digitalization. The aim of this research is to describe the Transformation of Islamic Education Leadership, Challenges for Islamic Education Leadership and Opportunities for Islamic Education Leadership in the Digital Era. This research uses an approach literature review. The data source for this research comes from Google Scholar, ChatGPT, You.com, Copilot and Educational Management journal database. The data analysis technique uses thematic analysis to examine the relationships and implications of the findings. The results of the analysis are then synthesized and interpreted to draw conclusions. The results of this research explain that Islamic education leaders must be able to integrate digital technology with the curriculum, maintain Islamic values, handle the digital divide and overcome resistance to change. Apart from that, infrastructure development and continuous training for educators are important to ensure the success of the transformation. The digital era also offers great opportunities to expand the reach and improve the quality of Islamic education, through access to resources, distance learning, international collaboration, use of social media, e-learning platforms, data analysis and artificial intelligence. So visionary and adaptive Islamic education leadership is needed to take advantage of opportunities and create an Islamic education system that is inclusive, effective and relevant.